Neurofilament Light Chain as a Biomarker for Monitoring the Efficacy of Transcranial Magnetic Stimulation on Alcohol Use Disorder - Zhang, Tian; Song, Bin; Li, Yanfei; Duan, Ranran; Gong, Zhe; Jing, Lijun; Wang, Kaixin; Ma, Bingquan; Jia, Yanjie (Frontiers in Behavioral Neuroscience, 2022)
Objective: This study assessed the effects of repetitive transcranial magnetic stimulation (rTMS) of the left dorsolateral prefrontal cortex (DLPFC) on serum neurofilament light chain (NfL) levels, alcohol consumption, craving, and psychological impairment in participants with alcohol use disorder (AUD). Methods: Participants with AUD were randomly assigned to receive one of two treatments (active or sham rTMS). All participants received 10 daily active or sham rTMS sessions over the left DLPFC for 2 weeks, with follow-up visits at baseline and immediately after the completion of the treatments. Serum samples were obtained before and after the intervention. Days of heavy drinking, visual analog scale (VAS) scores, and mental health component scores of the Medical Outcomes Study 36-Item Short Form Health Survey were used to assess the effects of rTMS. Results: Active rTMS had a significant effect on reducing days of heavy drinking, alcohol craving, and serum NfL levels, and improved social functioning and mental health. The improvement with active rTMS was significantly greater than that with sham rTMS. Correlation analysis revealed that the reduction in the baseline drinking level was positively correlated with declines in the VAS and NfL levels but not with psychological scores. Conclusion: rTMS of the left DLPFC was associated with reducing alcohol consumption and craving in patients with AUD and positively impacted neuropsychological and social function. Serum NfL levels may be useful as an early serological indicator of alcohol-induced brain injury.